Gambaran histologi hati dan ginjal mencit (Mus musculus L.) yang diinduksi karbon tetraklorida (CCl4) setelah pemberian ekstrak daun sirsak (Annona muricata L.) - Dewi, Ni Desak Made Aprilia; Wiratmini, Ngurah Intan; Sudirga, Sang Ketut (Jurnal Biologi Udayana, 2022)
Carbon tetrachloride (CCl4) is a chemical compound that is toxic, but is still often used in the refrigeration industry, fire extinguisher, and pesticide. Continuous use of CCl 4 can trigger the formation of free radicals, potentially damaging the liver and kidneys. Soursop ( Annona muricata L.) is a plant that can be used as an alternative medicine because it contains antioxidant compounds that can prevent free radical formation. This study aims to determine the effect of soursop leaf extract on the histopathology of mice ( Mus musculus L.) liver and kidneys induced by carbon tetrachloride. This research used a completely randomized design with 24 male mice, which were divided into 4 treatments consisting of negative control (K-) was given 0.5% Na-CMC solution, positive control (K+) induced by CCl 4 0,007 mL/20g BW which was dissolved in 0,1 mL coconut oil, and two treatments induced CCl 4 0,007 mL/20g BW and given soursop leaf extract at a dose of 100 mg/kg BW (P1) and 200 mg/kg BW (P2). Parameters observed in liver histology were fatty degeneration, hydropic degeneration, necrosis, congestion, and inflammatory cell infiltration. Parameters observed in kidney histology were fatty degeneration, necrosis, inflammatory cell infiltration, and glomerular swelling. The results showed that there was significantly different decrease in damage (p<0,05) in P1 and P2 compared to the positive control (K+) in liver and kidney histology incisions, it can be concluded that soursop leaf extract was able to repair liver and kidney damage after induced by carbon tetrachloride.